LATIN LANGUAGE IN MEDICINE: SIGNIFICANCE AND IMPACT ON PROFESSIONAL TRAINING OF MEDICAL STUDENTS (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The Latin language remains a cornerstone of medical terminology and plays a significant role in the professional training of medical practitioners. Though no longer a spoken language, Latin remains integral in medicine and healthcare systems worldwide. This article examines the role of Latin in the education of medical students and evaluates its impact on professional training through a study involving 30 first-year medical students. The findings suggest that proficiency in Latin terminology significantly enhances the learning process in anatomy, pharmacology, and clinical disciplines, leading to improved academic performance.